Pengembangan Modul Pembelajaran Berbasis Problem-Based Learning dengan Adobe Flash pada Mata Pelajaran Dasar Listrik Elektronika - Sari, Fenti Amelia; Usri, Hafiz (Jurnal Pendidikan Teknik Elektro, 2025)
This research aims to develop learning resources as a Module Based on Problem-Based Learning that is valid, practical, and effective on Basic Electrical and electronic subjects. The kind this research is Research and Development (R&D), and the development model is Ploomp, There are three steps: (1) preliminary research, (2) prototyping stage, and (3) assessment phase. The data analysis technique describes the validity, the practicality, and the effectiveness of the Learning Module Based on Problem-Based Learning for Basic Electrical Electronics. The learning module is designed using Adobe Flash CS3. The results who is obtained from this research are as follows: (1) The validity of the Learning Module Based on Problem-Based Learning is expressed as valid for the validation of the content, with total values are 0,93 dan 0,87, with category of valid and validation of performance with total value are 0,87 and 0,78. (2) The practicality Learning Module Based on Problem-Based Learning based on teacher response is expressed practical with a value 85 and the based-on students responses are expressed very practical with a value 84,71, (3) The effectiveness of Learning Module Based on Problem-Based Learning is expressed effective for improving the result of students learning because with 78,6% of students have reached KKM. Based on the results of this research, the Learning Module Based on Problem-Based Learning for Basic Electrical Electronics is valid, practical, and effective to be used as a resource for learning.